Quaternary dinoflagellate cysts in the Arctic Ocean: Potential and limitations for stratigraphy and paleoenvironmental reconstructions. (15th July 2018) - Matthiessen, Jens; Schreck, Michael; De Schepper, Stijn; Zorzi, Coralie; de Vernal, Anne
Abstract: The Arctic Ocean is a siliciclastic depositional environment which lacks any rock-forming biogenic calcareous and siliceous components during large parts of its Quaternary history. These hemipelagic sediments are nevertheless suitable for the study of organic-walled microfossils of which the fossil remains of dinoflagellates - dinoflagellate cysts - are the most important group. Dinoflagellate cysts have become an important tool in paleoceanography of the high northern latitudes, but their potential for Quaternary biostratigraphy has remained largely unexplored. Dinoflagellate cysts are the dominant marine palynomorph group which is more continuously present in the marginal seas (e.g. Barents Sea, Bering Sea) than in the Arctic Ocean itself throughout the Quaternary. Most species have long stratigraphic ranges, are temporary absent and show abundance variations on glacial-interglacial timescales. Of the more than 30 taxa recorded, only Habibacysta tectata and Filisphaera filifera became extinct in the Pleistocene. The highest persistent occurrence of H. tectata at ca. 2.0 Ma and the top of F. filifera acme at ca. 1.8 Ma can be used for supra-regional stratigraphic correlation between the Arctic Ocean and adjacent basins. These events corroborate a slow sedimentation rate model for the Quaternary section on the central Lomonosov Ridge, but a combination of different methods will have to be applied to provide a detailed chronostratigraphy. The occurrence of cysts of phototrophic dinoflagellates in certain stratigraphic intervals on Lomonosov Ridge supports published evidence of episodic opening of the multiyear Arctic sea ice cover during the Quaternary probably related to a stronger inflow of Atlantic water. This contradicts the hypothesis of a permanently ice covered central Arctic Ocean in the Quaternary. Highlights: Lower Pleistocene dinocyst events support slow sedimentation in central Arctic Ocean. a combination of different methods may provide a Quaternary chronostratigraphy. Cysts of phototrophic dinoflagellates suggest episodically ice-free central Arctic Ocean.